Hilary Putnam and the Nostalgia of Pragmatism - Faerna, Ángel (Analysis. Journal of Philosophical Research, 2018)
The aim of this paper is to offer a brief survey of the relationship between Hilary Putnam and pragmatism. In the first and second sections I comment on Putnam’s philosophical shift from “orthodox” analytic philosophy to “neopragmatism”, and take a look at his controversy with Richard Rorty concerning the meaning of pragmatism. The third section points at Putnam’s and Rorty’s rejection of the Peircean definition of truth as a key issue to account for the differences between neopragmatist philosophers and classic pragmatists (including Dewey). The final section draws some conclusions from the previous discussion concerning the “narrative” of contemporary pragmatism.